Cryptosporidium spp. CP15 and CSL protein-derived synthetic peptides’ immunogenicity and in vitro seroneutralisation capability (2018)
Cryptosporidium spp. is a zoonotic intracellular protozoan and a significant cause of diarrhoea in humans and animals worldwide. This parasite can cause high morbidity in immunocompromised people and children in developing countries, livestock being the main reservoir. This study was aimed at performing preliminary tests on Swiss albino weaned mice (ICR) to evaluate the humoral immune response induced against peptides derived from Cryptosporidium parvum CP15 (15 kDa sporozoite surface antigen) and CSL (circumsporozoite-like antigen) proteins. Peptides were identified and characterised using bioinformatics tools and were chemically synthesised. The antibody response was determined and the neutralising effect of antibodies was measured in cell culture. Despite all peptides studied here were capable of stimulating antibody production, neutralising antibodies were detected for just two of the CP15-derived ones. Additional studies aimed at evaluating further the potential of such peptides as vaccine candidates are thus recommended. © 2018 Elsevier Ltd